MODEL PENDIDIKAN KHULAFAUR RASYIDUN DAN IMPELEMENTASINYA BAGI PENDIDIKAN ISLAM DI INDONESIA - Riptono, Riptono; Bakri, Syamsul; Rohmadi , Yusup (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
This research will discuss the educational model developed by the Rasyidun Khulafaur. The Khulafaur Raysidun, consisting of four friends, namely Abu Bakar, Umar Ibn Khatam, Uthman Ibn Affan, and Ali bin Abi Talib provided different models or types of learning, but the essence of the teachings was taken from the Koran and the Sunnah of the Prophet. By using the library research method where the sources used are literature and then carrying out analysis with the most relevant sources to find answers to existing problems. The educational model implemented by Khulafaur Rasyidun apparently has different models. Abu Bakr as the first caliph to replace the Prophet Muhammad taught the educational model in the form of faith and moral education. Umar bin Khatam as the second caliph taught a model of education based on the physical framework, Uthman prioritized ethical education which focused on the study of morals, as did his last friend, Ali bin Abi Talib, who taught faith and morals education in forming a good Muslim person. The educational model taught by Khulafaur Rasyidun became the educational model used by the ulama after him. Where this education should also be carried out by Muslims today who are now starting to be attacked by Western-style education which is not in accordance with the soul and personality of their nation.